2016
DOI: 10.1007/s00253-016-7676-4
|View full text |Cite
|
Sign up to set email alerts
|

Site-directed mutagenesis of α-l-rhamnosidase from Alternaria sp. L1 to enhance synthesis yield of reverse hydrolysis based on rational design

Abstract: The α-L-rhamnosidase catalyzes the hydrolytic release of rhamnose from polysaccharides and glycosides and is widely used due to its applications in a variety of industrial processes. Our previous work reported that a wild-type α-L-rhamnosidase (RhaL1) from Alternaria sp. L1 could synthesize rhamnose-containing chemicals (RCCs) though reverse hydrolysis reaction with inexpensive rhamnose as glycosyl donor. To enhance the yield of reverse hydrolysis reaction and to determine the amino acid residues essential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…In addition to glycosidic bond cleavage, glycoside hydrolases (GHs) can be used for the synthesis of glycoside bonds in vitro via reverse hydrolysis reaction without the need for cofactors, such as uridine diphosphate (Lu et al 2015;Perugino et al 2004;Rosengren et al 2019;Xu et al 2016). Recently, several glycosidases, such as β-glucosidase, α-glucosidase, α-L -rhamnosidase, β-mannosidase and β-galactosidase, have been used to synthesize glycosides via the reverse hydrolysis reaction (Lu et al 2015;Arthornthurasuk et al 2018;Chen et al 2019;Ajisaka et al 2012;Tan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to glycosidic bond cleavage, glycoside hydrolases (GHs) can be used for the synthesis of glycoside bonds in vitro via reverse hydrolysis reaction without the need for cofactors, such as uridine diphosphate (Lu et al 2015;Perugino et al 2004;Rosengren et al 2019;Xu et al 2016). Recently, several glycosidases, such as β-glucosidase, α-glucosidase, α-L -rhamnosidase, β-mannosidase and β-galactosidase, have been used to synthesize glycosides via the reverse hydrolysis reaction (Lu et al 2015;Arthornthurasuk et al 2018;Chen et al 2019;Ajisaka et al 2012;Tan et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Honda et al (2008) reported that hydrogen-bonding interaction with catalytic water that reduced the hydrolytic reactivity of an inverting xylanase was dramatically decreased by eliminating the retention of the nucleophilic water molecule at the key amino acid residue. Other studies have focused on improving the hydrophobicity of the entrance to the active site (Xu et al 2016;Qin et al 2019;Frutuoso et al 2013) or acceptor subsite (Lundemo et al 2013). However, the effect of hydrophobicity of amino acid residues in the catalytic site on the catalytic activity needs to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The reverse hydrolysis product was determined using a TLC plate (Merck, Darmstadt, Germany) and HPLC 1200 system (Agilent). The TLC analysis was carried out using n‐butanol/ethanol/water (5:3:2, v/v/v) as the mobile phase (Xu et al ., ). Spots were visualised by carbonisation using a solution composed of 0.1% (w/v) 3,5‐dihydroxytoluene in H 2 SO 4 /methanol (2:8 v/v).…”
Section: Methodsmentioning
confidence: 97%
“…It has been used in debittering of citrus, manufacturing of prunin from naringin, enhancing of wine aromas, and producing of L-rhamnose (Yadav, Yadav, Yadav, & Yadav, 2010). Moreover, it is a biotechnologically important enzyme in food industry in the preparation of drug and drug precursors, and some α-l-rhamnosidases can catalyze the synthesis of rhamnose-containing chemicals by reverse hydrolysis (RCCs) with the L-rhamnose as a donor (Chin, Murad, Mahadi, Nathan, & Bakar, 2013;Martearena, Daz, & Ellenrieder, 2009;Xu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%